Rozdźwięki i współbrzmienia, czyli o naturze i kulturze w prozie Andrzeja Stasiuka - Setlak, Wiesław (Dydaktyka Polonistyczna, 2017)
Andrzej Stasiuk as an author of „travel” prose is equally strongly immersed in nature andculture. His narration is dominated by descriptions of nature. Man drawing both from nature andculture is important in his works. Stasiuk, an artist inevitably entangled in culture, sees an opportunity for self-fulfillment in nature understood as a more general notion than just natural environment.However, he does not pursue the „state of nature” – inculturation does not allow him to do it. Thus,he seeks a compromise consisting in „being” in „culture” while staying close to nature. The author’squest resemble the struggle of a nomad roaming some geographical space for a purpose. The samething happens when the writer tries to find a place for himself in the megaspace of nature and cultureusing the power of the mind and imagination. This type of activity is by geopoetics attributed toa socalled nomadological subject. It seems that the main thesis of Stasiuk’s literary anthropology isa conviction that man lives on the border of nature and culture where his existence can be authenticdespite certain antagonisms. In other words, consona is possible despite dissonance. It is all aboutproportion. Andrzej Stasiuk in his prose seems to be close to defining this very state of affairs.